"Wasting away": Diabetes, food insecurity, and medical insecurity in the Somali Region of Ethiopia. (May 2019) - Carruth, Lauren; Mendenhall, Emily
Abstract: Most research on diabetes has taken place in cities or in high-income countries, even though most diabetes deaths occur in low and middle-income countries, and diabetes disproportionately affects the poor. This research, by contrast, investigates rising concerns about diabetes among Somalis in eastern Ethiopia--in communities where obesity is rare and people face chronic food insecurity, forced displacement, recurrent humanitarian crises, and lack of access to medical care. Findings presented in this article build on ethnographic research with Somalis in eastern Ethiopia since 2007, and include anthropometric and demographic data collection with Somali diabetes patients and select adult siblings of these patients (n = 108) plus in-depth ethnographic interviews with a subset of the diabetes patients, their siblings, and medical providers serving Somali communities (n = 29) in July–August 2018. Most Somali patients we spoke with shared symptoms of progressive weight loss, weakness, and loss of teeth--or what people called "wasting away"--even when complying with prescribed pharmaceutical regimens and/or insulin. Diabetes and "wasting away" were characterized by Somalis as humoral pathologies; but rather than a consequence of obesity or pathological weight gain, these were perceived to be a consequence of stress, trauma, anger, displacement, loss of healthy fatness, and lack of access to fresh and healthy food over their lifetimes. Somalis' simultaneous experiences of progressive nutritional wasting and adult-onset diabetes echo how "tropical diabetes" was defined and experienced for thousands of years prior to the development of effective early diagnostics and biomedical treatments. This analysis therefore suggests heterogeneity and overlaps within and between categories of "type 1" and "type 2 diabetes" in populations with differential exposures to stress, crisis, and poverty. Exposures to food insecurity and medical insecurity, in particular, are pathogenic, and shape diabetes patients' clinical presentations and prognoses, as well as local etiologies and patterns of disease. Highlights: Food insecurity, medical insecurity, displacement, and crisis fuel diabetes among Somalis in Ethiopia. Somalis' diabetes symptoms include progressive weight loss and weakness, even on medications. Somalis describe diabetes as a humoral pathology, caused by stress, trauma, anger, and diet changes. Somalis' experiences highlight the heterogeneity and instability within diabetes disease categories. Clinical care for diabetes patients must address the pathogenicity of food and medical insecurity.